Doppler frequency estimation‐based handover algorithm for long‐term evolution networks. Issue 2 (1st June 2014) - Altrad, Omar; Muhaidat, Sami; Yoo, Paul D
Abstract : Mobile cellular radio systems have become complex multi‐layered systems with a mixed architecture of macro and micro cells; therefore, a dynamic method of triggering the handover algorithm in such systems is invaluable and required. In this paper the authors develop a simple handover mechanism to adapt for a fast moving mobile station requesting a handover, in which the authors utilise a Doppler frequency estimation in the downlink for adjustment and apply it to a long‐term evolution (LTE) network. This method is beneficial for high speed mobiles in macro and/or micro cells, in which for the latter the cell radius is small and needs a dynamic algorithm to respond in a timely manner. The main objective of this study is to investigate the performance of the proposed algorithm; hence, a system layout is specifically designed for this study. Other factors, such as interference, which may affect the performance of the suggested system are not addressed here. The main concern is to study and compare the proposed algorithm to the standard handover algorithm currently implemented in LTE. Simulations at the system level show a marked decrease in the average number of handovers requested.